Uruguay y el conflicto en Medio Oriente - Perazza, Federico (Revista Mexicana de Política Exterior, 2022)
In the 60 years since the United Nations was created, no other issue has demanded so much of the organization’s time and commitment as the Middle East conflict. Endless talks and negotiations have been held, and a great deal of effort has been channeled into follow-up activities. Since Israel was declared an independent state in 1948, it has been involved in no less than six wars with neighboring Arab states, with the ensuing loss of life (Israeli, Palestinian and Arab soldiers and civilians), not to mention the human desolation of the refugee camps that go hand-in-hand with the material destruction of war. In its ongoing search for a solution, the un has been forced to implement concrete, effective measures to deal with the political, economic and humanitarian toll of these Arab-Israeli wars. Federico Perazza looks at the stance the un has taken in the face of such a complex and long-lasting conflict of inextricable political, economic, military, religious, territorial and strategic dimensions. To manage the conflict, the un has resorted to peace-keeping operations, instruments not originally provided for in its Charter, but that have emerged as an ad hoc solution to the hostilities and wars unleashed since 1948. In this context, the author underlines the contribution of Uruguay —which played a prominent role in the partition of Palestine in 1947 and the subsequent creation of the State of Israel— to a peaceful solution to the conflict in the Middle East. Uruguayan troops have participated in peace-keeping missions in the zone, while the country has maintained a pacifistic vocation, as evidenced by the peace missions in sinab and those established as a result of the conflicts between Iraq and Iran and Iraq and Kuwait.